Turk Arch Pediatrics 2021
DOI: 10.5152/turkarchpediatr.2021.21166
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Vitamin D Prophylaxis on 25-OH Vitamin D Levels in Children

Abstract: Background: Vitamin D deficiency is a major public health problem. The aim of our study was to determine serum 25-hydroxyvitamin D levels among healthy children aged 3-36 months in a setting where vitamin D prophylaxis is a national policy for infants during the first year of life and among pregnant women. Methods: A total of 190 healthy children with a mean age of 15.9 ± 10.4 months were prospectively enrolled. Results: The mean 25-hydroxyvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…Due to the low content of Vit D in breast milk, it cannot meet the needs of rapid growth and development of infants and young children. Therefore, the baby is routinely given a certain dose of Vit D (preventive dose 400 IU/d) until the age of two years [12]. Infantile eczema is often accompanied by immune dysfunction and dysbiosis of the intestinal florae [7].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the low content of Vit D in breast milk, it cannot meet the needs of rapid growth and development of infants and young children. Therefore, the baby is routinely given a certain dose of Vit D (preventive dose 400 IU/d) until the age of two years [12]. Infantile eczema is often accompanied by immune dysfunction and dysbiosis of the intestinal florae [7].…”
Section: Introductionmentioning
confidence: 99%
“…It is common in children. Vitamin D level is thought to be <20 ng/mL in approximately one-third of children around the world, and deficiency is more common in adolescence 12 , 13 Vitamin D deficiency has been reported to be a risk factor for COVID-19 infection. It has been suggested that vitamin D supplementation will reduce infections that will cause hospitalization, and therefore vitamin D supplements should be taken to protect against COVID-19.…”
mentioning
confidence: 99%